Hydrotherapy Health Education to Reduce Blood Pressure in Hypertension - Meynur Rohmah; Tuti Wahyuningsih; Fitra Abdul Malik; Deby Mubarok (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The causes of hypertension in general are divided into two groups, namely primary and secondary. Primary hypertension is hypertension with no known cause such as heredity, age, gender, psychological pressure, stress, obesity (obesity), lack of exercise, and high cholesterol . While secondary hypertension is hypertension caused by other diseases such as narrowing of the arteries that supply blood to the kidneys, atherosclerosis (thickening of artery walls causing loss of elasticity of blood vessels). Foot soak hydrotherapy with warm water is one type of natural therapy that aims to increase blood circulation, reduce edema, increase muscle relaxation, nourish the heart, relax muscles, relieve stress, muscle aches, relieve pain, increase capillary permeability, provide warmth. on the body so that it is very useful for blood pressure reduction therapy in hypertension. This activity aims to increase people's knowledge about hydrotherapy health education on reducing blood pressure. The counseling method used leaflets and soaking the feet in warm water mixed with salt. After giving the material, participants know and understand the material that has been delivered by the speaker. Keyword s: Hypertension , Hydrotherapy , Blood pressure